AN ANALYSIS OF DIFFICULTIES IN PRONOUNCING DIPHTHONGS AND LONG VOWELS BY THE STUDENTS AT ALIYAH KINDERGARTEN - Yovika Sari (Literary Criticism, 2018)
The aims of the study are to know how many diphthongs and long vowels that can be mastered by the students at Aliyah Kindergarten and to investigate the difficulties in mastering diphthongs and long vowels experienced by the students at Aliyah Kindergarten. This research is descriptive qualitative research where the researcher collects the data observation, recording, taking notes, and analyzing based on Abdul Chaer (2003). Based on the obtained result, it can be concluded that there are 3 words of diphthongs that can be mastered by the students such as five, phone and here, while there are 2 words of diphthongs that are difficult to say, such as are grape and pear. Then, where are 3 word long vowels can be mastered by the students such as door, bee, and zoo, while the most difficult words spoken by the students are car and bird. Keywords: Diphthongs, Long Vowels, Phonology, Kindergarten.